Shelf Life Determination of Pegagan (Centella asiatica) Chips Using Accelerated Shelf-Life Testing (ASLT) Method - Wijanarti Sri; Ambarwati Galih; Sabarisman Iman (Agroindustrial Journal, 2020)
Pegagan (Centella asiatica) is a wild plant with various kinds of efficacies for health and usually as herbal or traditional medicine. Pegagan has been processed into various new products including chips. Pegagan Chips are hygroscopic product that easy to absorb water from the environment. The objective of this study was to determine the shelf life of Pegagan Chips packed in different type of packaging materials. The shelf life of Pegagan Chips was determined using Accelerated Shelf-Life Testing (ASLT) method with a critical moisture content approach. Two different types of packaging used were polyethylene (PE) plastic and standing pouch aluminum foil. The samples were stored at 28°C and RH 75%. The results showed that the shelf life of Pegagan Chips with PE plastic and aluminum foil standing pouch were 83 and 139 days, respectively. Aluminum foil standing pouch possessed lower packaging permeability which was 0.0603 g/m2.day.mmHg compared to PE plastic.